Fishes and other aquatic species in the Byzantine literature. Classification, terminology and scientific names. - CHRONE-VAKALOPOULOS, Maria; VAKALOPOULOS, Angelos (Byzantina Symmeikta, 2009)
Fishes and other aquatic species were substantial food in the every day life of Byzantine people. The predomination of Christianity contributed to the increased consumption of fishes and other seafood compared to the meat of land animals and chicken. More than a hundred ten names of fishes and about thirty names of other aquatic organisms are found in the sources of the Byzantine literature. Most frequent references are found in the medical texts of the Byzantine doctors, where, fishes are classified in categories depending on their physiology and origin, because, according to the writers, these are determining factors for the evaluation of the nutritional value of each species.The purpose of this study is to present the terminology of the fishes and the various aquatic species that are found in the Byzantine sources and to identify, in parallel, each species with its current scientific name.